Inclusion of Some Dehulled Legume Grains as Broiler Chicks Concentrates - Dousa , B.M.; Atti, Khadiga A. Abdel; Elseed, A.M. Fadel; Elawad, S.M. (International Journal of Poultry Science, 2011)
The objective of this study was to evaluate feeding plant concentrate (containing dehulled Faba bean, Cowpea and pigeon pea) substituting the imported concentrate for broiler chicks’ performance and blood parameters. Two hundred one-day old broiler chicks were divided into 4 groups of 50 birds in a completely randomize design (CRD) with five replicate (10 birds/replicate). Four experimental diets containing 0%, 5%, 7% and 9% plant concentrate were formulated to meet the nutrients requirements as outlined by NRC (1994). The study lasted for six weeks. Parameters measured was feed intake, body weight gain, Feed Conversion Ratio (FCR), pre-slaughter weight, dressing percentage, protein efficiency, some blood parameters and profitability. Result revealed that overall feed intake was not significantly (p>0.05) influenced by the dietary inclusion of plant concentrate. Increasing dietary level of plant concentrate had significantly (p<0.05) decreased weight gain and final body weight, while birds fed diet containing 5% plant concentrate observed similar (p>0.05) performance to the control group. There was no significant (p>0.05) difference on serum glucose, cholesterol, triglyceride, total lipids and total proteins, calcium and phosphorus. Birds fed 5% plant concentrate recorded similar (p>0.05) profit to that on control group.